If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+4)(2x-7)=90
We move all terms to the left:
(x+4)(2x-7)-(90)=0
We multiply parentheses ..
(+2x^2-7x+8x-28)-90=0
We get rid of parentheses
2x^2-7x+8x-28-90=0
We add all the numbers together, and all the variables
2x^2+x-118=0
a = 2; b = 1; c = -118;
Δ = b2-4ac
Δ = 12-4·2·(-118)
Δ = 945
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{945}=\sqrt{9*105}=\sqrt{9}*\sqrt{105}=3\sqrt{105}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-3\sqrt{105}}{2*2}=\frac{-1-3\sqrt{105}}{4} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+3\sqrt{105}}{2*2}=\frac{-1+3\sqrt{105}}{4} $
| X/2+x/3=x-9 | | x/8-4=0и-0,4x+9=0 | | -3+1/2x=-2 | | 2q-6=20 | | 5x-18=2x-8 | | 14x^2+31x+15=0* | | 6x+42=70-8x | | -3+1/2w=-2 | | 42-2x=x+36 | | q-1/3=-2/3 | | 8(4x─1)─12x=11(2x─6) | | 9x=2x-1 | | 54-2x=4x+36 | | (8x-16°)+(10x-32°)=180° | | t*8/3=336 | | 1/3(m-5)=3/4 | | 2x-5-4x+6=x | | 5/2x+2=0 | | 4.5x=2x-1 | | x*2/5=26 | | -3+x=-80 | | 2x-15=3x-20. | | (2/5)*x=26 | | 5v+8=-6+3v | | 9-x=-450 | | x^2+10x=-25. | | x^2=5x+36x2=5x+36 | | 14x-(3x-7)=95 | | m-8=18 | | 9n+5=5 | | 12g+8g=-12+11 | | 3(2x-3)-9=3x-27. |